Communities, crime prevention and the politics of articulation: A reply to Kit Carson - Hughes, Gordon (The Australian and New Zealand journal of criminology, 2004)
This article is a rejoinder to Kit Carson's seminal two-part essay, Is communalism dead? Reflections on the present and future practice of crime prevention. It aims to foster further debate on “the communal” in the field of crime prevention specifically, and in criminology more generally. In the first part of the article, an argument is made for a progressive discourse on communities built around the theory and practice of radical communitarianism. In the second part of the article, a debate is opened up on the continuing salience of appeals to communities in the contemporary governance of crime, disorder and safety. In particular, two questions — or provocations — are briefly explored in terms of “the instabilities of community governance” and what we may term the problem of “the stranger in community safety”. Finally, the article argues for the rethinking of the relationship of the communal and the critical criminological imaginar